2011
DOI: 10.1007/s11425-010-4134-0
|View full text |Cite
|
Sign up to set email alerts
|

Finite locally primitive abelian Cayley graphs

Abstract: Let Γ be a finite connected locally primitive Cayley graph of an abelian group. It is shown that one of the following holds: (1) Γ = Kn, Kn,n, Kn,n − nK 2 , Kn × · · · × Kn; (2) Γ is the standard double cover of Kn × · · · × Kn; (3) Γ is a normal or a bi-normal Cayley graph of an elementary abelian or a meta-abelian 2-group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…If p = 5, we have i = 6, 11, 16 or 21. Then a computation shows that S = a σ = {a, a 6 , a 11 , a 16 , a 21 } for all these four cases, that is, Σ satisfies (i) in Theorem 1.1(c).…”
Section: Jm Pan Z Liu Xf Yumentioning
confidence: 97%
See 1 more Smart Citation
“…If p = 5, we have i = 6, 11, 16 or 21. Then a computation shows that S = a σ = {a, a 6 , a 11 , a 16 , a 21 } for all these four cases, that is, Σ satisfies (i) in Theorem 1.1(c).…”
Section: Jm Pan Z Liu Xf Yumentioning
confidence: 97%
“…Recall the socle of a group is the product of all its minimal normal subgroups. According to the structure and to the action of the socle, the O'Nan-Scott theorem divides quasiprimitive permutation groups into eight types (see [29] [29] or [21]). Proof.…”
Section: Jm Pan Z Liu Xf Yumentioning
confidence: 99%
“…For instance, the cyclic graph C n is 2-distanceprimitive whenever n 4; the icosahedron (the graph in Figure 1) is 2-distance-primitive of valency 5; the family of 2-geodesic-transitive but not 2-arc-transitive graphs of prime valency provides an infinite family of such examples, refer to [13]. This family of graphs is also related to the class of well-known 'locally primitive graphs', see [19,22,23,24,30].…”
Section: Introductionmentioning
confidence: 99%
“…Godsil [7,Lemma 2.1] observed that N Aut( ) (T ) = T : Aut(T, S) where Aut(T, S) = {σ ∈ Aut(T )|S σ = S}. If Aut( ) = N Aut( ) (T ), then the graph was called a normal Cayley graph by Xu [24] and such graphs have been studied under various additional conditions, see [6,11,14,17,19]. In this paper, we classify the family of 2-geodesic transitive abelian Cayley graphs.…”
Section: Introductionmentioning
confidence: 99%